2020
DOI: 10.1016/j.pmedr.2020.101203
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in dietary behaviors among Japanese adolescents

Abstract: Highlights Few studies assessed a variety of adolescent dietary behaviours in Japan. The findings suggest that gender differences existed in dietary behaviors. Girls tended to adopt regular dietary behaviors as compared to boys. Schools support modeling and reinforcing healthy dietary behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…The current study revealed statistically significant association between gender,and nutritional knowledge and dietary lifestyle as revealed in previous studies (Otsuka et al, 2020;Grzymisławska, Małgorzata,Puch, Zawada,&Grzymisławski, 2020).Moreover, there was statistically significant between BMI and nutritional knowledge and practices. This finding was consistent with the results of previous studies (Valmórbida,Goulart,Busnello,&P ellanda,2017;Gutiérrez-Pliego,Camarillo-Romero,Montenegro-Morales&GarduñoGarcía,2016).…”
Section: Discussionsupporting
confidence: 86%
“…The current study revealed statistically significant association between gender,and nutritional knowledge and dietary lifestyle as revealed in previous studies (Otsuka et al, 2020;Grzymisławska, Małgorzata,Puch, Zawada,&Grzymisławski, 2020).Moreover, there was statistically significant between BMI and nutritional knowledge and practices. This finding was consistent with the results of previous studies (Valmórbida,Goulart,Busnello,&P ellanda,2017;Gutiérrez-Pliego,Camarillo-Romero,Montenegro-Morales&GarduñoGarcía,2016).…”
Section: Discussionsupporting
confidence: 86%
“…Females were more likely to skip breakfast intake than males, as they believed breakfast skipping helps to reduce weight [ 30 ]. It was reported that females are more concerned about their weight and have more body image distortion than males [ 31 ]. Skipping meals is often used as a weight-loss method [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the evidence on such association among adolescents came from the developed countries and there is a paucity in evidence coming from developing countries (15,16). Previous studies have also showed that adolescent girls are more likely to suffer from mental health problems but adhere to healthier dietary behaviours than boys (17,18). Therefore, it is important to quantify potential sex differences in the burdens of psychological distress and unhealthy dietary behaviours.…”
Section: Introductionmentioning
confidence: 99%